(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, A Place to Hang the Moon is a charming story. However, it was missing a certain “spark,” something particularly unique or memorable that would have made me enjoy it more.A note for sensitive or younger readers. There is a scene where William and Edmund have to go ratting with the rest of the village boys. William and Edmund are both horrified and sickened by the prospect of having to kill rats by hitting them with old boards. William ends up killing two rats, and while details really aren’t given, the scene could unsettle more sensitive readers. During WW11, Anna, Edmund, and William are evacuated from London to the countryside where it is safer from bombing. The children are seeking more than safety from bombs as they have just lost their grandmother, their only guardian, and are in need of a “forever” home. The children encounter cruelty, cold, and hunger. They find one place of comfort and refuge in the library; The librarian, Mrs. Müller becomes a significant person in their lives. With her, they experience cozy fires, hot chocolate, hot buttered thickly-sliced toast, bedtime stories, and someone who thinks they “hang the moon.”